2021
DOI: 10.1111/dom.14609
|View full text |Cite
|
Sign up to set email alerts
|

Performance of intermittently scanned continuous glucose monitoring systems in people with type 1 diabetes: A pooled analysis

Abstract: Aims: To conduct a pooled analysis to assess the performance of intermittently scanned continuous glucose monitoring (isCGM) in association with the rate of change in sensor glucose in a cohort of children, adolescents, and adults with type 1 diabetes. Material and Methods:In this pooled analysis, isCGM system accuracy was assessed depending on the rate of change in sensor glucose. Clinical studies that have been investigating isCGM accuracy against blood glucose, accompanied with collection time points were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…At least one study has observed differences in glycaemic variables assessed by CGM between normoglycemic individuals and people with impaired glucose tolerance [18], showing higher daytime average interstitial glucose concentrations and higher postprandial peaks in a group with abnormal glucose tolerance. In addition, studies examining the accuracy of CGM systems compared with glucose measurements from venous blood have provided inconsistent findings [1,15]. Therefore, the present study compared glucose responses assessed using the FreeStyle Libre2 TM CGM sensor with those obtained from venous plasma samples to investigate the accuracy of the sensor and its suitability for research purposes in healthy women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one study has observed differences in glycaemic variables assessed by CGM between normoglycemic individuals and people with impaired glucose tolerance [18], showing higher daytime average interstitial glucose concentrations and higher postprandial peaks in a group with abnormal glucose tolerance. In addition, studies examining the accuracy of CGM systems compared with glucose measurements from venous blood have provided inconsistent findings [1,15]. Therefore, the present study compared glucose responses assessed using the FreeStyle Libre2 TM CGM sensor with those obtained from venous plasma samples to investigate the accuracy of the sensor and its suitability for research purposes in healthy women.…”
Section: Introductionmentioning
confidence: 99%
“…The FreeStyle Libre TM CGM system is also commonly used for both clinical and research applications [8,[14][15][16]. The FreeStyle Libre TM sensors are factory-calibrated, which reduces the likelihood of inaccuracies compared to user-calibrated devices such as the Medtronic ENLiTE and Dexcom.…”
Section: Introductionmentioning
confidence: 99%
“…At the high end of the target range for most people (70-180 mg/dl) measured by CGMs, most of these products on the market function at approximately their published levels of accuracy, but at the low end of the target range, they are usually less accurate. 76 Several questions are currently unanswered (Table 2). With further research, it is hoped that the indications, benefits, and drawbacks of CGM for people without diabetes will become clearer.…”
Section: Potential Drawbacks Of Cgm Use By People Without Diabetesmentioning
confidence: 99%
“…The clinical accuracy of continuous glucose monitoring in patients with DM1 is shown in systematic reviews of randomized trials and meta-analyses by Teo et al, Moser et al, and Elbalshy et al (9)(10)(11). It is emphasized that future research should assess the precision and efficiency of CGM for various age groups and insulin therapy regimens.…”
Section: Introductionmentioning
confidence: 99%